2021
DOI: 10.1177/1055665621995047
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment Outcomes of Primary Alveolar Bone Grafts for Alveolar Clefts: A Qualitative Systematic Review

Abstract: Background: Alveolar bone grafting is utilized to manage alveolar clefts in patients with cleft lip and palate. However, the timing of bone grafting is variable with conflicting evidence supporting the use of primary alveolar bone grafting (PABG) in clinical practice. Primary Aim: To provide a qualitative systematic review analysis of long-term outcomes after PABG. Materials and Methods: A qualitative systematic review was performed following the Cochrane Handbook and reported using Preferred Reporting Items f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Previous studies have reported maxillary retrusion due to primary alveolar bone grafting [ 8 , 9 , 10 , 11 , 27 , 28 , 29 , 30 ], but others have reported successful outcomes when following presurgical orthopedic therapy [ 27 , 29 , 30 ]. Presurgical therapy with passive plates is known to reduce the cleft of the palate [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported maxillary retrusion due to primary alveolar bone grafting [ 8 , 9 , 10 , 11 , 27 , 28 , 29 , 30 ], but others have reported successful outcomes when following presurgical orthopedic therapy [ 27 , 29 , 30 ]. Presurgical therapy with passive plates is known to reduce the cleft of the palate [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the presented study of Groups A and B prompted changes in the surgical protocol at the study center. Primary alveolar bone grafting [ 10 ] and one-stage two-flap palatoplasty with secondary healing of lateral releasing incisions were abandoned. Following passive presurgical therapy, a one-stage protocol with bipedicled palatal flaps was implemented and modified for a continuous two-layer closure and primary healing [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABG has traditionally been classified as primary ABG (around 2 years), early secondary ABG (2–5 years), secondary ABG (6–12 years), and tertiary ABG (>12 years) according to chronological age [ 7 , 8 ]. By dental age, ABG can be divided into primary ABG (deciduous dentition), secondary ABG (mixed dentition), and tertiary ABG (permanent dentition).…”
Section: Surgical Timingmentioning
confidence: 99%
“…Maxillary dental arch transverse dimensions and dental arch relationships following different treatment protocols for patients with orofacial clefts have been the topic of studies and systematic reviews that evaluated treatment outcome in relation to different treatment parameters such as timing of palatal surgery in relation to craniofacial outcome ( Kappen et al, 2018 ), timing of primary alveolar bone grafting ( Carbullido et al, 2021 ), outcome of maxillary distraction ( Kloukos et al, 2018 ), and rehabilitation of the maxillary arch with a dental implant or an anterior fixed partial denture replacing the missing lateral incisor at the cleft side ( Caballero et al, 2019 ; Rezende Pucciarelli et al, 2020 ; Pucciarelli et al., 2021 ; Soares et al, 2021a ; Soares et al, 2021b ). However, those studies did not pay much attention to concomitant changes in the mandibular arch of patients with cleft lip and palate that occur after treatment.…”
Section: Introductionmentioning
confidence: 99%